2020
DOI: 10.2319/082919-562.1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of orthodontic appliance type on salivary parameters during treatment

Abstract: Objectives To evaluate the effect of orthodontic appliances on physicochemical, biochemical, and oxidative stress changes in salivary parameters during treatment. Materials and Methods A cohort study was conducted with 112 healthy patients. Salivary samples were taken at baseline, 1 month, and 9 months after placement of the orthodontic appliances used in treatment. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 28 publications
(25 reference statements)
0
17
0
Order By: Relevance
“…In this cohort study, 112 healthy patients were chosen and their salivary samples were taken at three time points. The results of this study showed salivary parameters of patients using aligners were less effected (11).…”
Section: Discussionmentioning
confidence: 63%
“…In this cohort study, 112 healthy patients were chosen and their salivary samples were taken at three time points. The results of this study showed salivary parameters of patients using aligners were less effected (11).…”
Section: Discussionmentioning
confidence: 63%
“…The characteristics of included studies are depicted in Tables 3 , 4 and 5 . This systematic review included 5 RCTs [ 12 , 17 , 26 , 27 , 31 ] and 9 NRSI [ 16 , 18 , 19 , 22 , 25 , 28 30 , 32 ]. Four of the included studies [ 12 , 29 – 31 ] investigated the incidence of WSLs, eight studies [ 16 – 18 , 22 , 26 28 , 32 ] investigated plaque accumulation as one of the primary outcomes and two studies [ 19 , 25 ] investigated SCB as primary outcome and plaque accumulation as additional outcome.…”
Section: Resultsmentioning
confidence: 99%
“…Alshahrani et al [ 41 ] reported significant reductions in the salivary flow rate and pH two months after commencing fixed orthodontic treatment and AlHudaithi and Alshammery [ 42 ] found significant reduction in salivary pH after four to five weeks of de-bonding or at the retention period. At the same time, Anu et al [ 43 ], Dallel et al [ 44 ], and Kouvelis et al [ 45 ] concluded that salivary pH did not significantly change between the studied time points during fixed orthodontic treatment.…”
Section: Discussionmentioning
confidence: 95%